Penerapan Model Kollaboratives Schreiben dengan Metode PORPE pada Keterampilan Menulis Bahasa Jerman Siswa Kelas XI SMA Taruna Nala - Katarina Agustin; Dewi Kartika Ardiyani (Singular: Journal of Pedagogical Language, Literature, and Cultural Studies, 2024)
This research aims to describe the application of the Kollaboratives Schreiben learning model with the PORPE method (Predict, Organize, Rehearse, Practice, Evaluate) and students' responses to its implementation in improving German writing skill of class XI students at SMAN Taruna Nala. Using a descriptive qualitative method, the study involved 16 students as research subjects. Data collection instruments included observation and questionnaires. Observation data were used to examine the implementation of the Kollaboratives Schreiben model with the PORPE method based on the lesson plan, while questionnaire data captured students' responses to the learning process. The results showed that students could follow the learning process in accordance with the PORPE method's stages and concepts. Based on the questionnaire data, the application of the Kollaboratives Schreiben model with the PORPE method is considered to help students in practicing retelling texts with the theme of introducing themselves and others (sich und andere Vorstellen). In general, the results of this study show that the application of the Kollaboratives Schreiben model with the PORPE method makes a positive contribution in practicing German text writing skill. In addition, students also show a positive response to the PORPE method as an interactive and interesting learning method.